Seed system security assessment: southern Malawi - International Center for Tropical Agriculture; Wellness and Agriculture for Life Advancement Program; Government of Malawi; Catholic Relief Services (International Center for Tropical Agriculture, 2011)
A Seed System Security Assessment (SSSA) was carried out across Southern Malawi in October 2011. It reviewed the functioning of the seed systems farmers use, both formal and informal, and assessed whether farmers could access seed of adequate quantity and quality in the short and medium term. The work covered 3 Districts, Zomba, Balaka and Chikhwawa, which were chosen to include a range of agro‐ecologies and possible seed security constraints. Field research encompassed: farmer interviews, seed/grain mar ket analysis, consultation with traders, focus group discussions (including discussions with women’s groups), and key -‐ informant sessions. Background papers were also commissioned on: a) the formal breeding sector’s structures and processes; b) the formal seed sector and fertilizer structures and processes; and c) current decentralized seed multiplication and distribution initiatives.